Comparing the Efficacy of Monthly Cyclophosphamide as Monotherapy versus Daily Fingolimod in Relapsing Remitting and Secondary Progressive Multiple Sclerosis - Vahid Shaygannezhad; Hassan Amini (مجله دانشکده پزشکی اصفهان, 2017)
Background: The aim of this study was to determine the efficacy of monthly cyclophosphamide and daily fingolimod in treatment of patients with multiple sclerosis (MS) and to compare these two treatment strategies.